Analysis of the Steady-Stream Active Flow Control for the Blended-Winged-Body Underwater Glider - Xiaoxu Du; Xin Liu; Yani Song (Journal of Marine Science and Engineering, 2023)
The BWB-UG is a glider with a smooth and integrated fuselage and wing. Its lift-to-drag properties are some of the most significant factors affecting its performance. In order to improve its hydrodynamic characteristics, the method of steady-stream active flow control (SS-AFC) is proposed. The computational fluid dynamics method is used to numerically investigate the SS-AFC of the BWB-UG. The mechanism of the SS-AFC effect on the lift-to-drag characteristics is revealed from the flow field aspect. The flow field of the BWB-UG before and after installing the SS-AFC was simulated using FLUENT. The results show that the SS-AFC can effectively optimise the hydrodynamic characteristics of the BWB-UG and can optimise the structure of the flow field around the BWB-UG. The steady-suction AFC can increase the lift-to-drag ratio of the BWB-UG by up to <semantics>45.01%</semantics>. With the steady-jet AFC, the lift-to-drag ratio of the BWB-UG can be increased by as much as <semantics>93.17%</semantics>.